The Contribution of Arabic in the Mass Media in the Spread of Islamic Da'wah - Burhanuddin; Marcella Putri Cahyani; Muhammad Wildan Baihaqi (al-Afkar, Journal For Islamic Studies, 2024)
Arabic has evolved in its function, not only as a language of religious studies that also reflects cultural identity, but as a major communication tool in the world of mass media to expand the reach of Islamic propagation with greater depth and accuracy. This research aims to explore the contribution of Arabic in the mass media to the spread of Islamic propagation. This research method uses descriptive qualitative. This method uses words and recounts the results of the research data to understand the influence of Arabic in delivering da'wah messages through mass media. As a result, the mass media, especially Rodja TV, Trans TV, and TV One are clear examples of the contribution of Arabic in Islamic da'wah in Indonesia. This is influenced by the integration of Muslims, to facilitate understanding of terms and strengthen their religious identity. In conclusion, Arabic contributes as a crucial tool of integration and understanding of religious terms in Islamic propagation through mass media, although it needs to be further improved for more effective communication.